The Motivation of Media Use and Using Instagram in Fulfilling Mental Health Information Needs - Drina Intyaswati; Dyandra Putri Divianti; Vina Mahdalena (Cita Konsultindo Research Center, 2022)
Mental health among young people needs attention; even more these days, the search for information related to mental health has risen sharply on social media. This study aims to evaluate the role of motives for media use and the use of Instagram @iamokay.id to fulfill the need for mental health information. The study used a survey method by distributing questionnaires to 100 respondents who were Instagram social media followers @iamokay.id. The theory underlying the research is the Theory of Uses and Gratification. This study uses a research model that places media use as a mediating variable of the relationship between motives and fulfilling information needs. In contrast, the previous literature placed media use as the independent variable. The findings show the direct influence of the motives for media use and the use of Instagram @iamokay.id on fulfilling the need for health information. In addition, using Instagram @iamokay.id mediates the relationship between the motives for media use and the fulfillment of mental health information needs. Instagram can be an alternative source of information for the general public to eliminate mental health among young people.